2022
DOI: 10.1136/bmjoq-2021-001459
|View full text |Cite
|
Sign up to set email alerts
|

Quality improvement in Kangaroo Mother Care: learning from a teaching hospital

Abstract: BackgroundKangaroo Mother Care (KMC) is a low-resource, evidence-based, high-impact intervention for low-birth weight (LBW) care. Quality improvement in KMC requires meso-level, macro-level and micro-level interventions. Our institution, a public teaching hospital, hosts a level-II/III neonatal intensive care unit (NICU). The average demand for beds typically exceeds available capacity, with 60% occupancy attributed to LBW patients. There was low uptake of KMC practice at our unit.Aim statementIn the initial p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…In a quality improvement study by Joshi et al, mothers found reclining chairs to be more comfortable than regular chairs and regular chairs were considered unacceptable for KMC sessions >1 hour. 21 Position of the infant was also shown to be a crucial aspect. Supported diagonal flexion (SDF) is an emerging concept that is shown to enhance maternal communicative behaviors and reduce the postpartum depression risk.…”
Section: (Table 2 Continued) (Table 2 Continued)mentioning
confidence: 96%
“…In a quality improvement study by Joshi et al, mothers found reclining chairs to be more comfortable than regular chairs and regular chairs were considered unacceptable for KMC sessions >1 hour. 21 Position of the infant was also shown to be a crucial aspect. Supported diagonal flexion (SDF) is an emerging concept that is shown to enhance maternal communicative behaviors and reduce the postpartum depression risk.…”
Section: (Table 2 Continued) (Table 2 Continued)mentioning
confidence: 96%
“…Reducing healthcare-associated infections by improving compliance to aseptic non-touch technique in intravenous line maintenance: a quality improvement approach 16 Improving donor human milk collection in a hospital without a human milk bank: a quality improvement initiative at an urban tertiary-care teaching hospital 18 Quality improvement in Kangaroo Mother Care: learning from a teaching hospital 26 Implementing use of sucrose analgesia in a standalone private facility level 3 neonatal care unit using point of care quality improvement methodology 20…”
Section: Neonatologymentioning
confidence: 99%
“…These studies have tested various interventions such as awareness of staff and parents, foster KMC, simpler KMC documentation, increasing resources such as KMC chairs and provision of bed to mother, rewarding staff and parents sequentially. [14][15][16][17][18][19] Either supervision or high intensity training (>5 days training combined with >1 interactive method) alone or even in combination is unable to bring greater changes in quality care. While low intensity training combined with QI collaborative has a greater impact on improving quality care in low-income and middleincome countries.…”
Section: Available Knowledge and Rationalementioning
confidence: 99%
“…These QI initiatives have implemented KMC ranging from 2 months to 9 months. These studies have tested various interventions such as awareness of staff and parents, foster KMC, simpler KMC documentation, increasing resources such as KMC chairs and provision of bed to mother, rewarding staff and parents sequentially 14–19…”
Section: Introductionmentioning
confidence: 99%